Case Report: A Chinese Family of Hypertrophic Cardiomyopathy Caused by a Novel Splicing Mutation in the FLNC Gene - Huang, Chunhui; Zheng, Yonghong; Zhang, Wei; Chen, Zhigang; Huang, Zhixin; Fang, Yuan (Frontiers in Genetics, 2022)
Hypertrophic cardiomyopathy (HCM) is primary cardiomyopathy with a genetic etiology, and it carries a high risk of diastolic dysfunction, heart failure, and malignant arrhythmias. We report the first familial HCM in China, caused by a novel FLNC splicing mutation. We performed duo exome sequencing (ES) to examine the genome of the proband and his mother. For ten days, a 15-year-old boy was presented to our hospital due to non-exercise-associated chest tightness and asthma. He was diagnosed with HCM [end-diastolic interventricular septal thickness was about 18mm by transthoracic echocardiography (TTE)]. His mother and sister performed TTE to screen familial cardiomyopathy, which revealed hypertrophic cardiomyopathy only in the proband’s mother. In ES of the mother-son duo identified a novel heterozygous mutation of the FLNC gene (chr7:128492808, NM_001127487, c.5905+2T>C, rs1808874360) as the candidate cause of autosomal dominant HCM. Sanger sequencing confirmed this novel mutation in the proband and his mother but absent in the proband’s sister. The potential impact of the novel mutation was predicted by MutationTaster, dbscSNV_ADA_SCORE, dbscSNV_RF_SCORE, CADD_phred, PhyloP20way_mammalian, PhyloP100way_vertebrate, SiPhy_29way_logOdds, and GERP++_RS software. After administration of furosemide, spironolactone, and metoprolol, the proband’s heart function was improved, and symptoms were alleviated. We present the first familial HCM caused by a novel FLNC splicing mutation via exome sequencing in China. Therefore, it is necessary that familial screening for patients with HCM should be performed for early detection of the HCM intervention in malignant cardiac events in advance and block genes.